The risk of social conflicts in the South Baltic Area in light of the location of factors of offshore wind farms - Piotr Biniek (Journal of Geography, Politics and Society, 2021)
Offshore wind farms have become one of the fastest growing renewable energy technologies in recent years. Projects developed in the area of the Polish Exclusive Economic Zone (EEZ) are considered crucial for the future of the energy sector in Poland. One of the arguments for the development of this sector is the common opinion among investors and decision makers that offshore wind farms are much less exposed to the risk of social conflicts compared to onshore installations. Due to the lack of completed investments in the Polish EEZ area and restriction of possible construction of farms to Baltic shoals only, explicit exclusion of the risk of protests seems wrong. The article identifies the factors of offshore wind farms OWF localization and the most important social groups at risk of participating in social conflicts. The Delphi method research indicates that, above all, numerous conflicts with other users of the maritime area should be expected, and the groups most vulnerable to conflict are fishermen, environmentalists, media and residents of coastal municipalities.